1994
DOI: 10.1111/j.1432-1033.1994.tb18671.x
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic stability and solution conformation of tandem G · A mismatches in RNA and RNA · DNA hybrid duplexes

Abstract: NOE and coupling-constant data show that all of the sugars are in the C3'-endo range of conformations, and glycosidic torsion angles are in the range -160" to -180" in r(CCACGGUGG) .r(CCACGAGUGG). Both sequential NOE intensities and circular-dichroism measurements indicate that the global conformation of the mismatched RNA is A-like. The N1H group of the mismatched guanine residue is not involved in hydrogen bonding with the adenine residue, indicating the presence of the amino-pairing scheme. Determination of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 44 publications
1
17
0
Order By: Relevance
“…one G and one A are on the same strand. Mismatches of GA type in DNA and RNA helices have been the subject of several studies in the past [14][15][16][17][18][19][20][21]. In the RNA folding, it is known that GA pairs contribute substantially to the RNA helix stability.…”
Section: Thermodynamic Outliersmentioning
confidence: 99%
“…one G and one A are on the same strand. Mismatches of GA type in DNA and RNA helices have been the subject of several studies in the past [14][15][16][17][18][19][20][21]. In the RNA folding, it is known that GA pairs contribute substantially to the RNA helix stability.…”
Section: Thermodynamic Outliersmentioning
confidence: 99%
“…4C, EC7ϩ2 Mismatched NDS). It is difficult to predict, however, which conformation is thermodynamically favored: although the dA:dG pair is stronger (30,31), rA is located at the end of the RNA oligonucleotide, and therefore, the rA:dG interaction in this context is less structurally constrained. The shift in the equilibrium between the two states of the 5Ј-end of the RNA toward the abnormally paired state determines the higher stability of the complex with mismatches in both the RNA and nontemplate DNA strands (Fig.…”
Section: Fig 2 Structural Analysis Of Pol II Ecs Obtained By Promotmentioning
confidence: 99%
“…GÁA mismatches in the socalled sheared base-pair con®guration, in which both nucleotides are in the anti conformation, and in which hydrogen bonds are formed between the guanine 2-amino to the adenine N7 and the guanine N3 to the adenine 6-amino were originally found in a DNA duplex (Li et al, 1991) and an RNA hairpin loop (Heus & Pardi, 1991), and have been observed in RNA at loop helix junctions (Szewczak et al, 1993;Szewczak & Moore, 1995;Biou et al, 1994;Pley et al, 1994a,b;Scott et al, 1995;Cate et al, 1996;Huang et al, 1996;Fountain et al, 1996;Jucker et al, 1996), within internal loops in RNA (SantaLucia & Turner, 1993;Katahari et al, 1994;Szewczak et al, 1993;Szewczak & Moore, 1995) as well as in DNA (Chou et al, 192;Lane et al, 1992;Katahari et al, 1993;Ebel et al, 1994;Maskos et al, 1993). Thermodynamic studies have revealed that the stabilities of tandem GÁA basepairs in RNA can range over almost 5 kcal mol À1 , depending on the closing base-pair (Walter et al, 1994).…”
Section: Introductionmentioning
confidence: 95%